Crunchies Krunchies House - Osman, Fadlillah; Jasni, Nurul Ain; Tony, Ervisster; Abd Arip, Ishak; Jungkin, Janet Binchos; Aspar, Siti Nazrinah (2013)
Crunchies Krunchies House is a company that gives the customers of traditional Sapit with new image where we still preserving the traditional taste of this product and hoping that the consumer will accepted this product as their regular consumption in their life. Our company produce two main product. First, the original traditional sapit. Second, the sapit will be in flavored of chocolate, peanut butter and peanut butter chocolate with varies of colour. This business is based in partnership where it consist six members. The members consist of General Manager, Administration Manager, Operational Manager, Marketing Manager and Financial Manager. The business capital is amounted to RM 160, 000 where the total contribution of each member is RM 60,000 and the rest is from Bank Islam loan. Our business will expected to commence on early September 2014 and our vision is to become the main and well-establish company that produced traditional Sapit internationally. By our marketing strategies which are maintain the good qualities where it can be purchasable and provide delivery services to our customers. It is supported by operation department that always maintain the good quality of our operation system which will increase our production quantities and administration department that keep-improving our company facilities. Also financing department that always find ways to minimize the cost of production and manage our account's flow.